"Bau Nyale " from the perspective of Science, Local Wisdom and Ecotourism - Ramdhani Sucilestari; Agus Ramdani; Susilawati Susilawati; AA Sukarso; Joni Rokhmat (Biota, 2023)
Bau Nyale is an annual tradition of the Sasak people in Central Lombok, which is celebrated every year on the 20th of the 10th month according to the Sasak calendar. This tradition comes from a legend that lives in society about the sacrifice of a princess to maintain the peace and unity of her country. Through a multidisciplinary approach that combines the perspectives of science and ecotourism sustainability, this study aims to present a comprehensive understanding of the Nyale legend and phenomenon and their associated ecotourism implications. This research method includes a literature study, field observations and interviews. The results of this study provide a deeper understanding of the legend of Princess Mandalika, the Bau Nyale phenomenon, and the related ecotourism implications. It was found that Nyale rituals have significant ecological and social impacts, including potential reductions in Nyale sea worm populations and changes to local culture. Therefore, sustainable ecotourism management is needed to ensure the sustainability of this phenomenon in the long term. This research has important implications in cultural preservation and environmental conservation. It is hoped that this study can contribute to an understanding of the interaction between cultural traditions and ecotourism and become a basis for developing sustainable management strategies in the context of the Bau Nyale phenomenon.